Telling tales: using stories to remake energy policy - Janda, K (Taylor and Francis, 2015)
To benefit and protect the populace, government policies often promise aspirational changes to current practice. Different kinds of narratives are important in the framing, explanation, motivation, and understanding of policies and strategies. For example, the UK government's 2008 Climate Change Act proclaimed that all new homes will be zero carbon by 2016. This ‘hero story’, where society is ‘saved’ by clever technologies, is inspiring, positive and familiar. An alternative is the ‘learning story’, where things are not quite as simple as they first seemed. In a learning story, protagonists are normal people who need to overcome a challenge. In energy policy, the learning story could address the gap between the technical potential and what is achieved in practice. Three real-world examples from retrofit and new-build projects are used to show how implicit narratives can create conflict when the tellers (e.g. researchers) have to tell one kind of story but have data for the other. Recommendations are provided for a balanced approach to the deployment of different kinds of tales by policy-makers, researchers, implementers and users. Harnessing the learning story and developing a ‘caring story’ could motivate policy-makers and the public to invest effort in building performance.